2014
DOI: 10.2196/jmir.3421
|View full text |Cite
|
Sign up to set email alerts
|

Daily Collection of Self-Reporting Sleep Disturbance Data via a Smartphone App in Breast Cancer Patients Receiving Chemotherapy: A Feasibility Study

Abstract: BackgroundImprovements in mobile telecommunication technologies have enabled clinicians to collect patient-reported outcome (PRO) data more frequently, but there is as yet limited evidence regarding the frequency with which PRO data can be collected via smartphone applications (apps) in breast cancer patients receiving chemotherapy.ObjectiveThe primary objective of this study was to determine the feasibility of an app for sleep disturbance-related data collection from breast cancer patients receiving chemother… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
181
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(184 citation statements)
references
References 16 publications
1
181
2
Order By: Relevance
“…There are several apps that allow users to report and analyze their sleep quality and duration, 6 but such data are often intrinsically subjective. In-laboratory polysomnography (PSG) is the gold standard for BRIEF SUMMARY Current Knowledge/Study Rationale: There are several preexisting, widely available, inexpensive smartphone apps designed to monitor sleep, but it is unclear whether they have clinical utility.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…There are several apps that allow users to report and analyze their sleep quality and duration, 6 but such data are often intrinsically subjective. In-laboratory polysomnography (PSG) is the gold standard for BRIEF SUMMARY Current Knowledge/Study Rationale: There are several preexisting, widely available, inexpensive smartphone apps designed to monitor sleep, but it is unclear whether they have clinical utility.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%
“…Limitations based on the exclusion of nearly a fourth of those screened in our study was not surprising; depressive symptoms have been reported in up to 63% of MPN patients in other studies. 8,11,13 Procedures for including a broader range of emotional/mental health compromised individuals will be developed for future studies, particularly because these very symptoms of emotional distress are known to be alleviated with mind-body practices such as yoga.…”
mentioning
confidence: 99%
“…Th e signifi cant and rapid availability of computers, tablets and smartphones, which in recent years has involved not only young people but also people of all ages and social classes, also allows to envision further use and implementation of this system through its computerized application, as already happens internationally 30 . Specifi cally, one might think to fi ll-in an online questionnaire in order to allow regular monitoring of patient symptoms, their performance status and their needs, as well as to obtain information on the patient health in real-time, thus improving effi ciency and quality of care, communication and help requests 31 .…”
Section: Discussionmentioning
confidence: 99%